Learners’ interaction with university staff units and administrations in distance learning - Mohammad, Ahlam Ibrahim (Journal of Educational and Psychological Sciences, 2021)
This paper provided an overview of the types of interactions in the distance learning environment mentioned in the literature, which are represented in the interaction of the learner with the content, the interaction of the learner with the teacher, the interaction of the learner with the learners, the interaction of the learner with the technological system and the interaction of the learner with the graphical interface. It added a sixth type related to the interaction of the learner with the employees of the university units and departments, such as the Admission and Registration Unit, the Academic Advising Unit and others.This type of interaction, we refer to, plays an important role in the distance learning process and when it occurs, it will likely help learners to cope with the technical and psychological problems they face and will drive their spiritual، social and physical growth, in addition to cognitive growth, that is through technical support services and curricular and extracurricular activities which provided by university's units and administrations. This paper also revealed the relationship between the different types of interaction, how they are affected by each other, and the dependence of some on each other, and it proposed a model that demonstrates this.
Keywords: distance learning; types of interaction; learners’ interaction